A Declarative Approach for Information Visualization - Oshiro, Adriane Kaori; Andrade, Andrea Rodrigues de; Pimentel, Maria da Graça (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2004: Anais do II Workshop em Tecnologia da Informação e da Linguagem Humana, 2004)
Information Visualization investigates the use of visual and interactive information representations with the aim of reducing users’ cognitive overhead as they analyze information. The objective of this work is to investigate mechanisms that allow presenting a large amount of information in Web-based platforms. We have built the iVIEW infrastructure that: (a) defines a declarative language based on XML Schema specifying a SVG-based visualization layout for information contained in XML documents; and (b) describes algorithms that execute the necessary steps to obtain a graphic representation of the information, implemented using XSLT. In this paper we describe the information elements and the visualization structures of iVIEW along with user-interaction resources. We also show the necessary steps for obtaining a graphic representation of the information using SVG.